Conflict Management in High-Stakes Illegal Drug Transactions - Bouchard, Martin (The British journal of criminology, 2021)
We draw from aspects of Black’s theory of conflict management to (1) provide a description of the types of disputes occurring at the highest levels of the drug trade and (2) examine whether conflicts that end in violence differed from those that found a peaceful resolution. A mixed-methods approach was used to analyse 33 incidents of smuggling transaction failures at the highest levels of the cocaine trade in the Netherlands. The results show that outcomes were determined by the way in which conflicts arose; lost product due to negligence and fraud increased the likelihood of violence. The fragile equilibrium between peaceful or violent resolution depended on whether the guilty party accepted blame or provided evidence that could account for losses.